Preparation method of electron beam curing coating with high color depth and soft hand feeling and application of electron beam curing coating in textile coloring
By using electron beam curing silicon modified colored particles and coatings on textiles, the problems of high energy consumption and limited penetration capacity of thermal curing and photocuring of textiles are solved, and the coloring of low-energy textiles with high color depth and soft feel are achieved, improving the coloring of low-energy textiles with high color depth and soft feel. Dye utilization and fabric breathability.
Patent Information
- Application Number
- CN202411259827.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Traditional thermal curing and tinting technology for traditional textiles consumes a long time, high energy consumption does not meet the requirements of low-carbon production, and photocuring technology is difficult to cure the non-color system. The existing electron beam curing technology causes the fabric to feel hard, have poor breathability, and have low dye utilization, and have low color depth. .
Design and develop electron beam cured silicon modified colored particles and coatings, and use electrostatic adsorption of carboxyl and cationic dyes in polymer segments by covalently "anchoring" small molecule dyes to improve soft and breathable properties, forming High-deep color and soft touch electron beam curing coating, suitable for textile coloring.
It achieves low energy consumption and rapid curing, the fabric is soft and breathable, and the breathability is close to the undyed state, which improves the dyeing rate and color depth of the dye, and solves the problems of high energy consumption and limited light curing penetration ability in traditional technologies.
Smart Images

Figure BDA0005035199310000071
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of an electron beam curing coating with high color depth and soft feel and application of the coating in textile coloring, belonging to the technical field of fine chemical industry. Background Art
[0002] Traditional textile coloring and curing are mainly thermal curing and photocuring. However, these methods have certain limitations. For example, the thermal curing process in ZL107938387B is time-consuming, energy-intensive, and has high production costs; photocuring is a technology that uses ultraviolet (UV) light sources for curing, which has the characteristics of fast speed and low energy consumption, such as ZL103788771B and ZL103788771B. However, limited by the penetration ability of light, light attenuation is closely related to the physical properties of the irradiated material. When the transparency of the material decreases, light penetration will be hindered, especially for opaque or thick materials. The penetration of light and the depth of energy deposition will be greatly reduced, making it difficult to apply photocuring to colored systems. With the increasing requirements for energy conservation and emission reduction, electron beam curing, as a new type of green curing technology with fast curing speed, low energy consumption, and no VOC gas emissions, has been widely used in printing, packaging, electronics, automobile manufacturing and other industries.
[0003] High water consumption, high energy consumption and high pollution have always been the key issues restricting the development of the textile industry. Therefore, a green printing and dyeing technology for textiles with low energy consumption and low water consumption is urgently needed. As a short-process and low-energy curing technology, the application of electron beam in textile coloring has rarely been reported. Due to the flexible and porous characteristics of textiles, the requirements of soft feel and breathability must be guaranteed while coloring. However, the current electron beam curing colorants do not take into account the factors of feel and breathability, resulting in a hard feel and poor breathability. In addition, the dyeing of fibers is a process of adsorption, diffusion and fixation, and in electron beam curing, the dyeing process is short, resulting in low utilization of the dye and low color depth. Summary of the invention
[0004] [Technical issues]
[0005] Traditional textile thermal curing coloring technology is time-consuming and energy-intensive, which does not meet the requirements of low-carbon production; light-curing coloring technology is limited by the penetration of light and is difficult to cure colored systems. Existing electron beam curing colorants will cause the fabric to feel hard and have poor air permeability, and the dye utilization rate is low, resulting in low color depth.
[0006] [Technical solution]
[0007] In order to solve the above problems, the present invention designs and develops an electron beam cured silicon modified coloring particle, an electron beam cured coating and its application in textile coloring. Specifically, the present invention relates to a polymer colorant that can be used for textile electron beam curing, and a small molecule colorant is covalently "anchored" in a polymer microsphere in a polymer segment, and the required functionality can be given by adjusting the structure of the polymer while protecting the dye. Its core material is a pigment or insoluble dye with color, and its shell material is a polymer that can be cured by electron beam irradiation, including a radiation-curable polymer monomer, an acrylic monomer with a carboxyl group and a polymerizable silicon monomer. By utilizing the electrostatic adsorption effect of carboxyl and cationic dyes, and compounding with cationic dyes, the cationic dyes can be adsorbed around the coloring particles, thereby improving the dye uptake rate. And by utilizing the softness and low surface energy of the polymerizable silicon monomer, the coating is given soft and breathable properties.
[0008] To achieve the above object, the present invention first provides an electron beam cured silicon modified colored particle; the colored particle is composed of a core material and a wall material; the core material includes a dye; the wall material includes a polymer that can be grafted by electron beam radiation polymerization. The polymer that can be grafted by electron beam radiation polymerization is copolymerized by a radiation curable polymer monomer, an acrylic monomer having a carboxyl group, and a polymerizable silicon monomer.
[0009] In one embodiment of the present invention, the mass ratio of the radiation-curable polymer monomer, the acrylic monomer having a carboxyl group and the polymerizable silicon monomer is 70-99:1-15:0.5-5.
[0010] In one embodiment of the present invention, the core-shell ratio of the core material to the wall material is 1:(1-4).
[0011] In one embodiment of the present invention, the dye includes at least one of olefin double bond anthraquinone type dyes, triarylmethane dyes, disperse violet 93, disperse blue 73, disperse blue 60, disperse yellow 64, disperse red 79, carbon black, phthalocyanine pigments, titanium white, and chrome green.
[0012] In one embodiment of the present invention, the radiation-curable polymer monomer includes at least one of acrylonitrile, polyurethane, ethylene-vinyl acetate copolymer (EVA), isobornyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, methacrylic acid, and glycidyl methacrylate.
[0013] In one embodiment of the present invention, the acrylic acid monomer having a carboxyl group includes at least one of acrylic acid, methacrylic acid, and vinyl acrylic acid.
[0014] In one embodiment of the present invention, the silicon polymerizable monomer includes at least one of vinyl trimethoxy silane (VTMS), vinyl polydimethyl siloxane (V-PDMS), divinyl tetramethyl disiloxane (DVMS), dimethyl vinyl chlorosilane, and vinyl triisopropoxy silane.
[0015] The present invention also provides a method for preparing electron beam cured silicon modified colored particles, comprising the following steps:
[0016] 4) Preparation of oil phase: Add polymer monomer, acrylic monomer and silicon polymerizable monomer into a beaker, mix and stir well to prepare oil phase;
[0017] 5) Preparation of nano-dispersion: The core material and the dispersant are mixed evenly, and grind and dispersed to 90-130 nm using a grinder at a speed of 5000-9000 rpm to obtain a nano-dispersion;
[0018] 6) Preparation of aqueous phase: Take the nano-dispersion obtained in step (2), add a dispersant and deionized water, and stir to prepare an aqueous phase;
[0019] 4) Preparation of emulsion: slowly add the oil phase prepared in step 1) to the water phase prepared in step 3), emulsify with a high-speed emulsifier, transfer the emulsified emulsion to a three-necked flask, and obtain an emulsion after mechanical stirring;
[0020] 5) Preparation of electron beam curable colored particles: Heat the emulsion obtained in step 3), reduce the rotation speed, slowly add the initiator to the emulsion several times, and react to obtain an electron beam curable colored particle dispersion; filter, centrifuge, wash and dry to obtain electron beam curable colored particles.
[0021] In one embodiment of the present invention, the core-shell ratio of the core material to the wall material is 1:1-4; wherein the mass fraction of the acrylic monomer with a carboxyl group in the oil phase is 1-15%; the mass fraction of the silicon polymerizable monomer in the oil phase is 0.5-5%, and the mass fraction of the radiation-curable polymer monomer in the oil phase is 70-99%.
[0022] In one embodiment of the present invention, in step (2), the dispersant includes one or more of sodium lignin sulfonate, DM1501, Span 20, Span 40, Span 60, DNS-86, SR-10, TMN-10, TMN-6, sodium p-styrene sulfonate, and DNS-628, and the mass ratio of the dispersant to the core material is 1:(0.5-3).
[0023] In one embodiment of the present invention, in step (3), the mass ratio of the nano-dispersion, the dispersant and water is 1:0.02-0.1:3-5.
[0024] In one embodiment of the present invention, in step (4), the mass ratio of the oil phase to the water phase is 1:7-15.
[0025] In one embodiment of the present invention, in step (5), the initiator comprises at least one of dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptylnitrile, persulfate, and azobisisobutylamidine dihydrochloride.
[0026] In one embodiment of the present invention, in step (5), the mass fraction of the initiator in the oil phase is 1-5%.
[0027] In one embodiment of the present invention, in step (5), the reaction temperature is 60-80° C. and the reaction time is 5-7 h.
[0028] In one embodiment of the present invention, the particle size of the electron beam cured silicon modified colored particles is 100-500 nm.
[0029] The present invention also provides an electron beam curing coating, which comprises, by mass percentage, 5-20% of the electron beam curing colored particles, 1-10% of a cationic dye, 1-5% of a dispersant, 1-10% of a crosslinking agent and the balance of deionized water.
[0030] The present invention also provides an application of the electron beam curing coating in coloring textiles, wherein the application is to apply the electron beam curing coating to the textiles by padding and then perform electron beam curing.
[0031] In one embodiment of the present invention, when the textile is finished by padding, the padding rate is controlled to be 70-100%, and the colored fabric can be obtained by electron beam curing.
[0032] The present invention also provides an electron beam curing coating, which comprises, by mass percentage, 5-20% of the electron beam curing colored particles, 1-10% of a cationic dye, 1-5% of a dispersant, 1-10% of a crosslinking agent, 0.5-10% of a thickener and the remainder of deionized water.
[0033] The present invention also provides an application of the electron beam curing coating in coloring textiles, wherein the application is to apply the electron beam curing coating to the textiles by printing or spraying, and then perform electron beam curing.
[0034] In one embodiment of the present invention, when finishing fabrics by printing or spraying, the coating viscosity is controlled at 100-1000 cps, and the coating is applied to textiles by printing or spraying, and electron beam curing is performed to obtain colored fabrics.
[0035] In one embodiment of the present invention, the printing method is one of screen printing, roller printing, and digital inkjet printing.
[0036] In one embodiment of the present invention, the spraying method is to use a spray gun to spray on the fabric dried at room temperature at intervals of 10-30 cm, a spraying speed of 10-30 cm / s, spraying in small amounts multiple times, and a spraying thickness of 20-200 μm.
[0037] In one embodiment of the present invention, the crosslinking agent includes one or more of hydroxyethyl acrylate, trimethylolpropane triacrylate, hydroxyethyl methacrylate, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, acrylic acid, and dodecyl methacrylate.
[0038] In one embodiment of the present invention, the thickener includes one or more of sodium alginate, xanthan gum, starch derivatives, carboxymethyl cellulose (CMC), methyl cellulose, and polyacrylic acid polymers.
[0039] In one embodiment of the present invention, the cationic dye includes one or more of cationic yellow X-8GLN, cationic golden yellow X-GL, cationic red GTL, cationic brilliant blue RL, cationic turquoise blue GB, cationic black WHL, and cationic blue M-RL.
[0040] In one embodiment of the present invention, the radiation dose of the electron beam curing is 10 kGy-80 kGy, and the curing time is 0.1-3 s.
[0041] The beneficial effects of the present invention are:
[0042] (1) The present invention provides a method for preparing an electron beam-cured coating with high color depth and soft feel and its application in textile coloring. Colored particles are formed by using a small molecule dye or pigment as a core and a polymer that can be cured by electron beam radiation as a shell. The prepared colored particles can be mixed with other dyes, dispersants, cross-linking agents, etc. to prepare an electron beam-cured colored coating. The colored coating is used to pad-dye a textile substrate, and the fabric is cured under electron beam conditions, which can greatly reduce the curing energy consumption.
[0043] (2) Silicon polymerizable monomers are added to the wall material, and the prepared colored particles are used to dye the fabric. The fabric obtained has good softness and good air permeability, and the air permeability can reach up to 93.2% of that before dyeing.
[0044] (3) The addition of acrylic acid monomers with carboxyl groups introduces carboxyl groups into the shell layer. The carboxyl groups can adsorb cationic dyes, increase the dye uptake rate, and achieve high color depth.
[0045] (4) The present invention has the characteristics of fast curing speed and low energy consumption, which solves the problems of long curing process and high energy consumption of traditional textile coloring and curing technology, as well as the difficulty in curing colored systems due to the limitation of light penetration ability. At the same time, it achieves the problems of high color depth and soft hand feel, and solves the difficulty of electron beam curing in textile applications. DETAILED DESCRIPTION
[0046] The present invention is further described below through specific examples, but the embodiments of the present invention are not limited thereto.
[0047] Embodiment 1:
[0048] (1) A method for preparing electron beam cured silicon modified colored particles
[0049] Weigh 30g of Disperse Yellow 64, 45g of dispersant DNS-86 and 225g of water, add 1 / 3 of the total volume of zirconium beads, put into a horizontal grinder and grind at a speed of 6000rpm until the particle size is 110nm to obtain a nano-dispersion. Take 10g of the nano-dispersion and add it to a beaker, add 35g of deionized water and 0.5g of dispersant DNS-86 to prepare an aqueous phase; weigh 2g of acrylonitrile, 1g of hydroxyethyl acrylate, 0.3g of acrylic acid and 0.09g of vinyltrimethoxysilane, mix and stir evenly to obtain an oil phase.
[0050] The aqueous phase was placed in a three-necked flask and mechanically stirred at 600 rpm. The oil phase was slowly added to the system and stirred evenly. The temperature was raised to 70°C. 3 mL of an aqueous solution containing 0.05 g of azobisisobutylamidine dihydrochloride was added at a rate of 20 s / drop. After reacting for 2 h, 2 mL of an aqueous solution containing 0.05 g of azobisisobutylamidine dihydrochloride was added. After reacting for another 3 h, 3 mL of an aqueous solution containing 0.05 g of azobisisobutylamidine dihydrochloride was added. After reacting for 1 h, the solution was cooled to room temperature, filtered, and centrifuged to obtain electron beam cured colored particles.
[0051] (2) Preparation method of electron beam curing coating
[0052] The electron beam cured colored particles prepared in Example 1 were weighed in an amount of 10% of the coating, and cationic yellow 28 accounting for 3% of the coating mass, trimethylolpropane triacrylate accounting for 10% of the coating mass, dispersant SR-10 accounting for 5% of the coating mass and the balance deionized water were added to prepare an electron beam cured coating.
[0053] (3) Application of electron beam curing coatings in textile coloring
[0054] The electron beam curing coating prepared in step (2) is used to finish the fabric by a double dipping and double rolling method, the liquid carrying rate is controlled to be 90%, and electron beam curing is performed with an energy of 50 kGy and a curing time of 1 s to obtain an electron beam cured colored fabric.
[0055] The air permeability, K / S value, fabric strength, dye grafting rate, color fastness and hand feel of the fabric prepared by the above method were evaluated. Air permeability test: The air permeability of the fabric was tested using an air permeability meter in accordance with GB / T5453-1997 "Determination of air permeability of textile fabrics". The K / S value was tested by randomly selecting two points on the fabric using a Datacolor 650 colorimeter, and the value represents the depth of the color. The hand feel performance test was tested using a PhabrOmeter3 instrument in accordance with standard FBW04003. The friction fastness was tested using the method of GB / T 3920-2008.
[0056] Example 2
[0057] The electron beam cured colored particles prepared in Example 1 were weighed, and the amount was 10% of the coating mass, and 5% of the coating mass was added with dispersant SR-10, 10% of the coating mass was added with trimethylolpropane triacrylate, 10% of the coating mass, and 10% of the thickener DM-5221G and the balance of deionized water, and the coating viscosity was controlled at 800cps to obtain a printing coating. The fabric was printed by screen printing, and electron beam curing was performed, with an energy of 50kGy and a curing time of 1s to obtain an electron beam cured colored fabric.
[0058] Example 3
[0059] The electron beam-cured colored particles prepared in step (1) of Example 1 were weighed in an amount of 10% of the mass of the coating, and a dispersant SR-10 accounting for 5% of the mass of the coating was added. Trimethylolpropane triacrylate accounting for 10% of the mass of the coating and the balance water were added to obtain a spray coating. The surface of the fabric was coated by spraying at an interval of 30 cm and a spraying speed of 10 cm / s. The spraying was performed in small amounts and multiple times. After the spraying was uniform, electron beam curing was performed at an energy of 50 kGy and a curing time of 1 s to obtain an electron beam-cured colored fabric.
[0060] Example 4
[0061] The acrylonitrile in step (1) of Example 1 is adjusted to ethylene-vinyl acetate copolymer.
[0062] Example 5
[0063] The trimethylolpropane triacrylate in step (2) of Example 1 was adjusted to dodecyl methacrylate.
[0064] Example 6
[0065] The electron beam curing energy of Example 1 was adjusted to 70 kGy, and other conditions remained unchanged.
[0066] Comparative Example 1
[0067] The electron beam curing energy in Example 1 was adjusted to 5 kGy, and other conditions remained unchanged.
[0068] Comparative Example 2
[0069] The electron beam curing energy in Example 1 was adjusted to 100 kGy, and other conditions remained unchanged.
[0070] Comparative Example 3
[0071] The difference between Comparative Example 3 and Example 1 is that in step (2), the electron beam cured colored particles prepared in Example 1 are weighed in an amount of 10% of the mass of the coating, trimethylolpropane triacrylate accounting for 10% of the mass of the coating is added, dispersant SR-10 accounting for 5% of the mass of the coating and the balance deionized water are added to prepare the coating, and the coating is prepared by a double dipping and double rolling method, with the liquid rate controlled to 90%, dried at 60°C, and then baked at 160°C for 3 minutes.
[0072] Comparative Example 4
[0073] The difference between Comparative Example 3 and Example 1 is that in step (2), the electron beam-cured colored particles prepared in Example 1 are weighed in an amount of 10% of the mass of the coating, trimethylolpropane triacrylate accounting for 10% of the mass of the coating is added, SR-10 accounting for 5% of the mass of the coating and the balance deionized water are added, a two-immersion and two-rolling method is adopted, the liquid carrying rate is controlled to 90%, and ultraviolet light in the 465nm band is used for curing, the distance is 15cm, and the curing time is 5min.
[0074] Comparative Example 5
[0075] The amount of trimethylolpropane triacrylate in step (2) of Example 1 was adjusted to 0%, and other conditions remained unchanged.
[0076] Comparative Example 6
[0077] The electron beam cured colored particles in Example 1 were adjusted to Disperse Yellow 64, and other conditions remained unchanged.
[0078] Comparative Example 7
[0079] The amount of Cationic Yellow 28 in Example 1 was adjusted to 0%, and other conditions remained unchanged.
[0080] Comparative Example 8
[0081] The spray coating in step (2) of Example 1 is adjusted to an electron beam curing coating, which is composed of 50% polyurethane acrylate, 15% tripropylene glycol diacrylate, 15% pentaerythritol triacrylate, 5% pigment yellow 139, 10% dispersant BYK-163, 2% leveling agent VOK-3777 and 3% adhesion promoter dh-7340, and other conditions remain unchanged.
[0082] Comparative Example 9
[0083] The amount of vinyltrimethoxysilane in Example 1 was adjusted to 0 g, and other conditions remained unchanged.
[0084] Comparative Example 10
[0085] The preparation method of the electron beam cured colored particles in Example 1 is adjusted as follows: 12g acrylonitrile, 2g acrylic acid and 0.6g vinyl trimethoxysilane are weighed, 1g Disperse Yellow 64 is dissolved in the system to prepare an oil phase; 10g dispersant DNS-86 and 25g water are evenly dissolved to prepare an aqueous phase. The aqueous phase is placed in a three-necked flask and stirred evenly at a speed of 600rpm, and the oil phase is slowly added to the system, the temperature is raised to 70°C, 5ml of acrylonitrile solution containing 0.8g azobisisobutyronitrile is added at a speed of 20s / drop, and the reaction is performed for 5h; the temperature is cooled to room temperature, filtered, centrifuged, and washed to obtain electron beam cured colored particles.
[0086] Table 1 Properties of electron beam cured colored fabrics
[0087]
[0088] It can be seen from Examples 1 and 6 and Comparative Examples 1 and 2 that the electron beam radiation intensity is too low to achieve the dye curing effect. Increasing the electron beam radiation intensity can slightly increase the dye grafting rate and K / S value, but will seriously damage the fabric.
[0089] It can be seen from Example 1 and Comparative Example 3 that although the electron beam radiation curing is slightly inferior to the high temperature curing in terms of K / S value and color fastness, the energy consumption is significantly reduced.
[0090] It can be seen from Example 1 and Comparative Example 4 that electron beam curing can solve the problem that it is difficult to cure colored systems in UV curing systems, and is superior to UV curing in all aspects.
[0091] It can be seen from Example 1 and Comparative Example 6 that electron beam curing will cause small molecule dyes to cleave and fail to complete curing grafting. Using polymers to covalently anchor the dyes can avoid the cleavage problem, thereby increasing the grafting rate of the colored particles.
[0092] It can be seen from Example 1 and Comparative Example 7 that the dyeing rate and K / S value can be greatly improved by using the compound with cationic dyes, and the cationic dyes are attracted by the anionic groups on the surface of the colored particles, thereby improving the color depth.
[0093] It can be seen from Example 1 and Comparative Example 8 that, compared with commercially available electron beam-cured colorants, the colorant of the invention has significantly improved hand feel and air permeability retention.
[0094] It can be seen from Example 1 and Comparative Example 9 that the use of silane helps to increase the grafting rate and significantly increase the feel and air permeability retention rate of the treated fabric.
[0095] It can be seen from Example 1 and Comparative Example 9 that after the core material is prepared into a nano-dispersion, the dyeing rate of the fabric can be significantly improved, and the hand feel and air permeability retention rate of the treated fabric are also significantly increased.
[0096] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. An electron beam cured silicon modified colored particle, characterized in that: The colored particles are composed of a core material and a wall material; the core material includes a dye; the wall material includes a polymer that can be grafted by electron beam radiation polymerization; wherein the polymer that can be grafted by electron beam radiation polymerization is copolymerized by a radiation-curable polymer monomer, an acrylic monomer with a carboxyl group and a polymerizable silicon monomer.
2. The colored particle according to claim 1, characterized in that The mass ratio of the radiation-curable polymer monomer, the acrylic monomer with a carboxyl group and the polymerizable silicon monomer is 70-99:1-15:0.5-5. The radiation-curable polymer monomer includes at least one of acrylonitrile, polyurethane, ethylene-vinyl acetate copolymer, isobornyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, methacrylic acid, and glycidyl methacrylate. The acrylic monomer with a carboxyl group includes at least one of acrylic acid, methacrylic acid, and vinyl acrylic acid. The silicon polymerizable monomer includes at least one of vinyltrimethoxysilane, vinyl polydimethylsiloxane, divinyltetramethyldisiloxane, dimethylvinylchlorosilane, and vinyltriisopropoxysilane.
3. The colored particle according to claim 1, characterized in that The core-shell ratio of the core material to the wall material is 1:1-4, and the core material includes a dye, and the dye includes at least one of olefin double bond anthraquinone dyes, triarylmethane dyes, disperse violet 93, disperse blue 73, disperse blue 60, disperse yellow 64, disperse red 79, carbon black, phthalocyanine pigments, titanium white, and chrome green.
4. The method for preparing silicon-modified colored particles according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Preparation of oil phase: Add polymer monomer, acrylic monomer and silicon polymerizable monomer into a beaker, mix and stir well to prepare oil phase; 2) Preparation of nano-dispersion: The core material and the dispersant are mixed evenly, and grind and dispersed to 90-130 nm using a grinder at a speed of 5000-9000 rpm to obtain a nano-dispersion; 3) Preparation of aqueous phase: Take the nano-dispersion obtained in step (2), add a dispersant and deionized water, and stir to prepare an aqueous phase; 4) Preparation of emulsion: slowly adding the oil phase prepared in step 1) into the water phase prepared in step 3), wherein the mass ratio of the oil phase to the water phase is 1:7-15, emulsifying with a high-speed emulsifier, transferring the emulsified emulsion into a three-necked flask, and mechanically stirring to obtain an emulsion; 5) Preparation of electron beam curable colored particles: Heat the emulsion obtained in step 3), reduce the rotation speed, slowly add the initiator to the emulsion several times, and react to obtain an electron beam curable colored particle dispersion; filter, centrifuge, wash and dry to obtain electron beam curable colored particles.
5. The preparation method according to claim 4, characterized in that: In step (2), the dispersant includes one or more of sodium lignin sulfonate, DM1501, Span 20, Span 40, Span 60, DNS-86, SR-10, TMN-10, TMN-6, sodium p-styrene sulfonate, and DNS-628, and the mass ratio of the dispersant to the core material is 1:0.5-3.
6. The preparation method according to claim 4, characterized in that: In step (3), the mass ratio of the nano-dispersion, the dispersant and the water is 1:0.02-0.1:3-5.
7. The preparation method according to claim 4, characterized in that: In step (5), the initiator includes at least one of dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptylnitrile, persulfate, and azobisisobutylamidine dihydrochloride, the mass fraction of the initiator in the oil phase is 1-5%, and the particle size of the electron beam cured silicon modified colored particles is 100-500nm.
8. An electron beam curing coating, characterized in that: Calculated by mass percentage, the components include 5-20% of the electron beam cured colored particles according to any one of claims 1 to 3, 1-10% of a cationic dye, 1-5% of a dispersant, 1-10% of a crosslinking agent, 0-10% of a thickener and the balance of deionized water.
9. The electron beam curing coating according to claim 8, characterized in that: The crosslinking agent includes one or more of hydroxyethyl acrylate, trimethylolpropane triacrylate, hydroxyethyl methacrylate, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, acrylic acid, and dodecyl methacrylate; the thickener includes one or more of sodium alginate, xanthan gum, starch derivatives, carboxymethyl cellulose, methyl cellulose, and polyacrylic acid polymers; and the cationic dye includes one or more of cationic yellow X-8GLN, cationic golden yellow X-GL, cationic red GTL, cationic brilliant blue RL, cationic turquoise blue GB, cationic black WHL, and cationic blue M-RL.
10. Use of the electron beam curing coating according to claim 8 or 9 for coloring textiles, wherein the electron beam curing coating is applied to the textiles by padding, printing or spraying, and then electron beam curing is performed, the radiation dose of the electron beam curing is 10 kGy-80 kGy, and the curing time is 0.1-3 s.
Citation Information
Patent Citations
A blue light curable ink composition for textiles and its digital inkjet printing curing method
CN103788771B
A method for preparing binder-free, polymeric colored latex particles for inkjet printing.
CN107938387B
Electron beam curing coating
CN105440933A
Acrylate polymer emulsion containing pigment particles and preparation method thereof
CN106349424A
Pigment / organosilicon / polyacrylate nano capsule paint having multilayer core-shell structure and application thereof
CN108589343A